PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDS METHODIST SUNGAI BAKAU KECAMATAN SINABOI - Antosa, Zariul Antosa; ', Lasma; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Problem background of this research is most of student  guess answer the question. Interesting of student in IPA lesson is low. It is shown that only few of students that ask the teacher and answer the questions.  The average score result of IPA  test is still low, that is 61,5. And only 7 of 20 student or 35% in class can reach standard of KKM, while score of KKM is 65. This is the problem: “Do the Cooperative Learning Model type STAD improve IPA studying result, Students of class V SDS Methodist Sungai Bakau Kecamatan Sanaboi Kabupaten Rokan Hilir?”. This research form is Observation of Class Action/ Penelitian Tindakan Kelas (PTK). This is the hypothesis of this research: “If the Cooperative Learning Model type STAD is applied therefore gets to increase IPA studying results, Student of class V SDS Methodist Sungai Bakau Kecamatan Sinaboi Kabupaten Rokan Hilir”. This research is done as much 2 cycles with 6 appointments, there are 4 presentations and 2 times of test. After that, data is collected and analyzed. Test I (UH I) shows the increasing average score, from basic score 61,5 to 75,5, it increases 13,75 points (18,3%). And at the Test II (UH II) increase about 12,75 points (14,75%). So that, the average score is to be 88. So, total increasing from basic score to Test II (UH II) is 26,5 points (30%). The Classically Completing activity also increase about 35%, score percentage 35% at the Test I to be 70%. And at the Test II, percentage score is 95%, it increases 25%. Besides that, activity of teacher and student are increasing in every meeting. Percentage of teacher activity at the first meeting is 58,33%, and at the second is 70,83% (increase 12,5%). Fourth meeting, percentage of teacher activity is 83,33% (12,5%), and 91,67% (8,3%) at the fifth meeting. Student activity at the first meeting is 54,17%, and 62,5% (increase 8,33%) at the second meeting. There is increasing to be 83,33% (20,83%) at the fourth meeting, and 95,83% (12,5%) at the fifth meeting. So, the conclusion is the Implementation of Cooperative Learning Model type STAD can improve IPA studying result, Students of class V SDS Methodist Sungai Bakau Kecamatan Sanaboi. Keywords: Cooperative Learning Model type STAD, IPA studying result